Reliability and validity of the inline skating skill test - Radman, I.; Ruzic, L.; Padovan, V.; Cigrovski, V.; Podnar, H. (Journal of Sports Science & Medicine, 2016)
This study aimed to examine the reliability and validity of the inline skating skill test. Based on previous skating experience forty-two skaters (26 female and 16 male) were randomized into two groups (competitive level vs. recreational level). They performed the test four times, with a recovery time of 45 minutes between sessions. Prior to testing, the participants rated their skating skill using a scale from 1 to 10. The protocol included performance time measurement through a course, combining different skating techniques. Trivial changes in performance time between the repeated sessions were determined in both competitive females/males and recreational females/males (-1.7% [95% CI: -5.8-2.6%] - 2.2% [95% CI: 0.0-4.5%]). In all four subgroups, the skill test had a low mean within-individual variation (1.6% [95% CI: 1.2-2.4%] - 2.7% [95% CI: 2.1-4.0%]) and high mean inter-session correlation (ICC = 0.97 [95% CI: 0.92-0.99] - 0.99 [95% CI: 0.98-1.00]). The comparison of detected typical errors and smallest worthwhile changes (calculated as standard deviations × 0.2) revealed that the skill test was able to track changes in skaters` performances. Competitive-level skaters needed shorter time (24.4-26.4%, all p < 0.01) to complete the test in comparison to recreational-level skaters. Moreover, moderate correlation (? = 0.80-0.82; all p < 0.01) was observed between the participant`s self-rating and achieved performance times. In conclusion, the proposed test is a reliable and valid method to evaluate inline skating skills in amateur competitive and recreational level skaters. Further studies are needed to evaluate the reproducibility of this skill test in different populations including elite inline skaters.